Pengaruh Islamic branding, kualitas produk, lokasi dan harga terhadap keputusan pembelian konsumen Muslim pada produk Rabbani Store di Solo Raya - Ahmad Indarta; Rahayu Tri Utami; Yesi Faworo (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2023)
This study aims to test whether there is an influence on Islamic branding, product quality, location, and price variables on the decision of Muslim solo raya consumers to purchase products at Rabbani stores. This study took a population from the Muslim community in Soloraya with a total sample of 112 respondents using a cluster sampling technique. The research material comes from surveys made using Google Forms and the SPSS application. Validity and reliability tests are used in device testing. Meanwhile, for multiple linear regression analysis, processing of the T-test, processing of the F-test, and the coefficient of determination were used to analyze the data. Obtaining the data tested shows that Islamic branding, product quality, location, and price simultaneously drive purchasing decisions with an F-Test score and a significant probability value of 0.000 <0.05. Thus, these four variables have a significant influence on the decision of Muslim Solo Raya consumers to make purchases at Rabbani stores